2022
DOI: 10.1186/s12933-022-01568-8
|View full text |Cite
|
Sign up to set email alerts
|

Circulating metabolites and molecular lipid species are associated with future cardiovascular morbidity and mortality in type 1 diabetes

Abstract: Background Cardiovascular disease remains the leading cause of mortality in individuals with diabetes and improved understanding of its pathophysiology is needed. We investigated the association of a large panel of metabolites and molecular lipid species with future cardiovascular events in type 1 diabetes. Methods The study included 669 individuals with type 1 diabetes. Non-targeted serum metabolomics and lipidomics analyses were performed using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…We have previously investigated the associations between circulating metabolites and lipid species and diabetic complications in T1D, both cross-sectionally and prospectively 4–9. Through these studies, we have identified hydroxybutyrate isomers, ribose derivatives, and branched-chain amino acids that were associated with presence and development or progression of DR,8 kidney disease,5 and cardiovascular disease 10. Similar results were also identified in relation to cardiac autonomic neuropathy 4 11.…”
Section: Introductionmentioning
confidence: 57%
“…We have previously investigated the associations between circulating metabolites and lipid species and diabetic complications in T1D, both cross-sectionally and prospectively 4–9. Through these studies, we have identified hydroxybutyrate isomers, ribose derivatives, and branched-chain amino acids that were associated with presence and development or progression of DR,8 kidney disease,5 and cardiovascular disease 10. Similar results were also identified in relation to cardiac autonomic neuropathy 4 11.…”
Section: Introductionmentioning
confidence: 57%
“…Lipidomic analysis is a new technique that identifies a broad range of lipid species, which could uncover some variables potentially associated with chronic complications in this population [10]. Preliminary data from our group also showed that some dietary-related lipid parameters could identify individuals with T1D more prone to suffer from CVD [11,12].…”
Section: Introductionmentioning
confidence: 81%
“…In this sense, some previous studies from the Scandinavian population showed that this lipid variable was directly associated with worse kidney [37][38][39] and coronary heart disease outcomes [39]. Nevertheless, other studies using a more powerful lipidomic analysis (which could identify up to 106 different molecular lipid species) showed that several sphingomyelin subclasses were associated with worse kidney outcomes and cardiovascular mortality while other subclasses were associated with better outcomes [10,38]. Furthermore, no significant relationships were found between any of the sphingomyelin subclasses and stroke [10].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cardiovascular disease is a common complication in patients with diabetes [ 8 , 21 ]. A large number of scholars have conducted intensive research on diabetes-related cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%